PENGARUH TANAMAN SELA SORGUM MANIS TERHADAP PERTUMBUHAN TANAMAN KARET BELUM MENGHASILKAN - Sahuri Sahuri (Jurnal Agroteknologi, 2017)
The Land between row of immature rubber period has a potential to produce sweet sorghum. This sorghum is one of high value commodities for food and energy security due to its wide adaptation. The objective of this research were to study the effect of rubber+sorghum intercropping system on the growth of immature rubber trees and to study some agronomic parameters of sorghum and production of sweet sorghum as rubber intercrops. The experiment was conducted at the Sembawa Research Station from June to October 2013. The experiment was carried out as a single factori using Randomized Block Design with three replications. The treatment were 3 varieties of sorghum i.e: Pahat, Kawali and Mandau. Observation of rubber trees was conducted using simple random sampling method, comparing the rubber trees growth of sorghum intercropping system with the rubber trees growth of monoculture system. The results showed that sorghum had a positive effect on the growth of rubber tree IRR 118. Furthermore, fresh stem weight (37.11 t/ha), juice yield (1.80 t/ha), and grains yield (2.69 t/ha) of sweet sorghum Kawali higher than that of the varieties tested. The Kawali has a high potential to produce a biofuel because it had a highest fresh stem weight and juice content.